Ditch management using low-grade weirs: an opportunity for mitigating water quality and quantity impacts - Strock, J. S.; Ranaivoson, A. Z. (Frontiers in Environmental Science, 2025)
To improve productivity, extensive agricultural areas in the Midwest United States require drainage systems consisting of subsurface drainage (tile) and open ditches. Transport of sediment, pathogens, pesticides, and nutrients from runoff and drainage from crop fields contributes to eutrophication and degradation of surface waters. Solutions are needed to improve environmental quality and reduce the negative impacts from runoff and agricultural drainage systems. This study assessed the effect of low-grade weirs on discharge and nitrate-nitrogen concentration and loss from a pair of experimental drainage ditches. One control (without weirs) and one treatment (with weirs) ditch were studied from 2017 through 2023 at the University of Minnesota, Southwest Research and Outreach Center near Lamberton, MN, United States. This study was the first evaluation of agricultural ditches, with and without low-grade weirs, and their potential to mitigate discharge and nitrogen loss in a cold climate. Stage-discharge data were collected using a data logger and bubble level sensor. Water samples were collected for water quality analysis daily using automated samplers. Analysis of the data was conducted using paired t-tests and a paired analysis approach. Analysis of covariance and linear regression of the treatment ditch against the control ditch were highly significant for nitrate-nitrogen concentration and load. The ditch with the low-grade weir was found to significantly decrease nitrate-nitrogen concentration and load. More specifically, the treatment ditch reduced discharge, nitrate-nitrogen concentration and load by 51%, 22% and 58%, respectively. The greatest discharge from the ditches occurred in March while most nitrogen losses occurred between May and June. This study provides evidence and highlights the potential of ditches equipped with low-grade weirs to reduce nitrate-nitrogen losses when compared to ditches without low-grade weirs in a cold climate. In addition, the study also emphasizes the importance of climate as a driver of nitrate-nitrogen loss from crop lands and ditches which is amplified by monthly precipitation variability.